2019
DOI: 10.1371/journal.pone.0216575
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous melatonin accelerates seed germination in cotton (Gossypium hirsutum L.)

Abstract: Seed germination is considered the beginning of the spermatophyte lifecycle, and it is a crucial stage in determining subsequent plant growth and development. Although many previous studies have found that melatonin can promote seed germination, the role of melatonin in cotton germination remains unexamined. The main objective of this study is the characterization of potential promotional effects of melatonin (at doses of 0, 10, 20, 50, 100 and 200 μM) on cotton seed germination. This experiment demonstrated t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 112 publications
(74 citation statements)
references
References 63 publications
6
68
0
Order By: Relevance
“…To inhibit excessive generation of ROS, plants possess a complex enzymatic defense system to combat oxidative damage (Souza et al, 2014;Ahammed et al, 2020c). SOD and POD act as important antioxidant enzymes that can eliminate redundant ROS from plant tissues, protecting the plasma membrane from peroxidation (Xiao et al, 2019;Ramachandra et al, 2004). In plant cells, SOD can rapidly convert O 2 − to form H 2 O 2 and O 2 , while H 2 O 2 can be further scavenged by other antioxidant enzymes .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To inhibit excessive generation of ROS, plants possess a complex enzymatic defense system to combat oxidative damage (Souza et al, 2014;Ahammed et al, 2020c). SOD and POD act as important antioxidant enzymes that can eliminate redundant ROS from plant tissues, protecting the plasma membrane from peroxidation (Xiao et al, 2019;Ramachandra et al, 2004). In plant cells, SOD can rapidly convert O 2 − to form H 2 O 2 and O 2 , while H 2 O 2 can be further scavenged by other antioxidant enzymes .…”
Section: Discussionmentioning
confidence: 99%
“…The accumulation of ROS induces lipid peroxidation and the degradation of unsaturated fatty acids, producing MDA, which causes damage to the seed structure and reduces seed germination (Rajjou & Debeaujon, 2008;Xiao et al, 2019). Previous studies have shown that the application of exogenous MT significantly suppressed MDA accumulation under abiotic stressors in several plant species (Ahammed et al, 2019b;Hasan et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cotton is the world's second-most important oil crop and a crucial textile fibre crop (Xiao et al, 2019). The formation of crop yield is a complex process of the interaction between source and sink (Chen et al, 2019), and the morphological and physiological characteristics of the roots are closely related to the growth and development of the aboveground parts (Niu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%